ChemInform Abstract: Methods of Synthesis: 1, 3, 4‐Thiadiazole‐2‐thiones: A Review. Issue 47 (4th November 2013) - Khatale, Pravin N.; Sivakumar, T.; Mahajan, Niranjan S.; Kature, D. V.
Abstract Review: 29 refs.